2007
DOI: 10.1136/jech.2006.052696
|View full text |Cite
|
Sign up to set email alerts
|

Does the school fruit and vegetable scheme improve children's diet? A non-randomised controlled trial

Abstract: The SFVS promoted an increase in fruit intake after three months. At seven months the effect remained significant but reduced, and it returned to baseline in year 2 when pupils were no longer part of the scheme. There was a small impact on the intake of some nutrients across the children surveyed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
85
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 6 publications
6
85
2
4
Order By: Relevance
“…Sodium levels were high as has been shown in many dietary surveys of children (4,22) . Large regular intakes of savoury snacks contribute to these high intakes of sodium.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Sodium levels were high as has been shown in many dietary surveys of children (4,22) . Large regular intakes of savoury snacks contribute to these high intakes of sodium.…”
Section: Discussionsupporting
confidence: 51%
“…Power calculations suggested that a sample of 2200 children would give approximately 90 % power to detect a difference of 0?33 portions of fruit per day based on a comparison of mean fruit intake in schools with a high proportion of children eligible for free school meals v. those with a low eligible proportion. Results from our initial evaluation of the SFVS found a 68 % response from pupils completing the CADET food diary (4) . To allow for this loss to follow-up, 130 schools would be recruited with an estimated total of 3250 children available.…”
Section: Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…School programmes for increased F&V consumption may include one or several components, including, for example, specific F&V projects in food and health subjects, parental involvement, school cafeteria interventions and actual provision of F&V to the pupils, either free or at a subsidized price (3,(8)(9)(10)(11)(12)(13)(14)(15)(16) . Experiences from this last type of intervention -actual provision of F&V to the pupils -have generally been positive, although the evidence on whether it leads to sustained increases in F&V intake 2-3 years after the intervention period is both scarce and mixed (3,(8)(9)(10)(11) .…”
mentioning
confidence: 99%
“…Experiences from this last type of intervention -actual provision of F&V to the pupils -have generally been positive, although the evidence on whether it leads to sustained increases in F&V intake 2-3 years after the intervention period is both scarce and mixed (3,(8)(9)(10)(11) .…”
mentioning
confidence: 99%